The derivative on the value relevance through tax avoidance and earnings control - Suhendra, Suhendra; Murwaningsari, Etty; Mayangsari, Sekar (Linguistics and Culture Review, 2022)
This investigation expects to inspect and analyze the effect of derivative transactions on earnings management, the role of corporate tax avoidance in moderating effect of derivative transactions on earnings management, the effect of earnings management worth pertinence of earnings, and the effect of derivative transactions Worth Pertinence of earnings. This examination utilizes information from non-monetary organizations in Indonesia and Thailand for the period 2013-2017 with 91 test of organizations. This investigation, earnings management is calculated based on the Jaggi model and the Jaggi changed model. The value relevance of earnings is calculated based on Ohlson's model. Corporate tax avoidance is calculated based on the book tax difference. The results show that subordinate exchanges have a constructive outcome on earnings management. Corporate tax avoidance has not been proven to strengthen the effect of derivative transactions on earnings management. Earnings management adversely influences the worth pertinence of earnings. Derivative transactions negatively affect the value relevance of earnings. Derivative transactions, especially those with non-hedging criteria, show a high tendency towards earnings management activities. Intercountry testing, derivative transactions have a positive effect on earnings management in Indonesia while in Thailand it does not.